Visual evoked potentials show strong positive association with intracranial pressure in patients with cryptococcal meningitis - Marcelo Adriano da Cunha Silva Vieira; Maria do Amparo Salmito Cavalcanti; Dorcas Lamounier Costa; Kelsen Dantas Eulálio; Otoni Cardoso do Vale; Chrystiany Placido de Brito Vieira; Carlos Henrique Nery Costa (Arquivos de Neuro-Psiquiatria)
Objective : To verify the relationship between intracranial pressure and flash visual evoked potentials (F-VEP) in patients with cryptococcal meningitis. Method The sample included adults diagnosed with cryptococcal meningitis admitted at a reference hospital for infectious diseases. The patients were subjected to F-VEP tests shortly before lumbar puncture. The Pearsons linear correlation coefficient was calculated and the linear regression analysis was performed. Results : Eighteen individuals were subjected to a total of 69 lumbar punctures preceded by F-VEP tests. At the first lumbar puncture performed in each patient, N2 latency exhibited a strong positive correlation with intracranial pressure (r = 0.83; CI = 0.60 - 0.94; p < 0.0001). The direction of this relationship was maintained in subsequent punctures. Conclusion : The intracranial pressure measured by spinal tap manometry showed strong positive association with the N2 latency F-VEP in patients with cryptococcal meningitis.